ANALISIS PENGARUH MARKETING PUBLIC RELATION DAN SALES PROMOTION TERHADAP KEPUTUSAN PEMBELIAN PUPUK PHONSKA BERSUBSIDI PT. PETROKIMIA GRESIK ( Studi di Kabupaten Sragen ) - Eliza Nurul Kharitsah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to analyze the influence of Marketing and Public Relations and Sales Promotion on purchasing decisions Phonska subsidized fertilizer PT. Petrokimia Gresik in Sragen. To find out how much influence the dependent variable (buying decisions) to the independent variables (Marketing Public Relation and Sales Promotion) used regression analysis with analytical methods test t and f. This study uses a sample of 100 farmer that use Phonska Phonska subsidized fertilizer PT. Petrokimia Gresik . While sampling using purposive sampling techniques. The results of studies using multiple linear regression analysis, showed that simultaneous variable Marketing Public Relation (X1) and Sales Promotion (X2) has a significant influence on buying decisions (Y). While partial, variable Marketing Public Relation and Sales Promotion showed a significant effect on decision buying consumen. Keyword : Marketing Public Relation, Sales Promotion, Decision Buying